2014
DOI: 10.1002/bsl.2150
|View full text |Cite
|
Sign up to set email alerts
|

How Common is “Common Knowledge” about Child Witnesses among Legal Professionals? Comparing Interviewers, Public Defenders, and Forensic Psychologists with Laypeople

Abstract: The present study evaluates the knowledge of jury-eligible college students (n = 192), investigative interviewers (n = 44), forensic psychologists (n = 39), and public defenders (n = 137) in regard to the research on interviewing children. These groups' knowledge was compared with the scientific research on the impact of interview techniques and practices on the accuracy of child witnesses. Jury-eligible students were the least knowledgeable, but their accuracy varied widely across items. Both interviewers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…For example, in studying adults’ disclosures of life experiences, Pasupathi et al (2009) found that previously nondisclosed (e.g., omitted or denied) events were significantly more emotionally negative and less emotionally positive than previously disclosed events. Moreover, many adults believe that interviewers should ask children leading questions to elicit disclosure of negative experiences, such as child sexual abuse (Buck, Warren, Bruck, & Kuehnle, 2014; Quas, Thompson, & Clarke-Stewart, 2005). These studies suggest that adults are sensitive to the possibility that children, like adults, may not readily disclose negative self-relevant information.…”
Section: Event Valencementioning
confidence: 99%
“…For example, in studying adults’ disclosures of life experiences, Pasupathi et al (2009) found that previously nondisclosed (e.g., omitted or denied) events were significantly more emotionally negative and less emotionally positive than previously disclosed events. Moreover, many adults believe that interviewers should ask children leading questions to elicit disclosure of negative experiences, such as child sexual abuse (Buck, Warren, Bruck, & Kuehnle, 2014; Quas, Thompson, & Clarke-Stewart, 2005). These studies suggest that adults are sensitive to the possibility that children, like adults, may not readily disclose negative self-relevant information.…”
Section: Event Valencementioning
confidence: 99%
“…Experts' understanding of witness suggestibility and jurors' lack thereof (Buck et al, 2014; McAuliff & Kovera, 2007; Quas et al, 2005) demonstrates that expert testimony on these issues should satisfy the helpfulness requirement of FRE Rule 702 and therefore be admissible in court. Courts that routinely disallow witness suggestibility expert testimony on the grounds that it is not helpful to jurors would be wise to reconsider their reasoning accordingly.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…We abhor CSA in the abstract, but as a society we fail to act against it (Cheit and Freyd 2005). Recent research reveals that misconceptions about CSA are still quite common both among laymen and professionals (Calvert and Munsie-Benson 1999;Benton et al 2006;Rubin and Berntsen 2007;Legault and Laurence 2007;Magnussen et al 2010;Antrobus et al 2012;Magnussen and Melinder 2012;Houston et al 2013;Buck et al 2014;French and Ost 2016). Misconceptions, including inappropriate expectations toward primary and secondary CSA victims 7 can seriously endanger the process and result of investigation.…”
Section: Resultsmentioning
confidence: 99%